Substrate specificity analysis of semi-purified fibrinolytic protease of Metabacillus sp. CS-2 to support its potential as a wound debridement agent - Pardosi, Sola Grace Afika; Zilda, Dewi Seswita; Rahmani, Nanik; Saptaningtyas, Ragil; Salleh, Mohd Nazil; Ethica, Stalis Norma (Edelweiss Applied Science and Technology, 2024)
Fibrinolytic proteases play an important role in the fibrin degradation process, which is crucial in the treatment of chronic wounds as a debridement agent. Fibrinolytics work by breaking down fibrin tissue that forms as part of a blood clot leading to cell necrosis. Metabacillus sp. CS-2 is known to be one of the potential sources of fibrinolytic protease production with high activity. This study aims to examine the activity and specificity of fibrinolytic proteases produced by Metabacillus sp. CS-2 before and after the ultrafiltration process by zymography. In this study, crude protease extraction was carried out from Metabacillus sp. CS-2 followed by ultrafiltration to improve the purity and activity of the enzyme. The obtained ultra-filtrate protease was then characterized for its specificity to 4 protein substrates, i.e. casein, gelatine, fibrin, and collagen. The results showed that the activity of the fibrinolytic protease enzyme from Metabacillus sp. CS-2 was improved by ultrafiltration from 0.342  0.011 to 0.768 0.014 U/mL min-1. The obtained zymogram confirmed that the protease of Metabacillus sp. CS-2 can degrade all of the protein substrates tested. Interestingly, the most specific substrate for Metabacillus sp. CS-2 was fibrin evidenced by intense clear zone smeared from high to low enzyme sizes. In conclusion, ultrafiltration is proven to be effective in increasing the activity of fibrinolytic proteases. The ability to degrade fibrin and collagen substrates likely supports fibrinolytic protease of the strain to function as a debridement agent in wound healing treatment.